Contribution of capsular and lipopolysaccharide antigens to the pathogenesis of Klebsiella pneumoniae respiratory tract infection - Chhibber, S; Aggarwal, S; Yadav, V (Folia microbiologica, 2003)
The role of Klebsiella pneumoniae K- and O-polysaccharide antigens was determined in a rat model of lobar pneumonia. The induction of experimental infection in rats by wild-type strain, and its lipopolysaccharide- and capsular polysaccharide-deficient mutants was compared. Though the mutant lacking both antigens (K- O-) induced infection it could not successfully establish itself in the rat lung. It caused only mild infection, as compared to the wild type strain (K+ O+) and the strain lacking CPS alone (K- O+). Besides capsular polysaccharide, the lipopolysaccharide antigen was shown to be an important factor in pathogenesis of K. pneumoniae acute respiratory tract infection.
Keywords: Bacterial Capsules; Lipopolysaccharides; Rats; Klebsiella pneumoniae; Virulence; Antigens, Bacterial; Animals; antigeny bakteriální; bakteriální pouzdra; krysa rodu Rattus; Klebsiella Infections; Respiratory Tract Infections; zvířata; lipopolysacharidy; virulence; infekce bakteriemi rodu Klebsiella; infekce dýchací soustavy